2009
DOI: 10.1007/s11356-009-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, biological, and ecotoxicological assessment of pesticides and persistent organic pollutants in the Bahlui River, Romania

Abstract: Future close monitoring will be necessary for insuring compliance with the Water Framework Directive, and for refining standards and understanding of the local situation, but with relevance for the wider international community. On the basis of the situation described in the present study, we recommend that future studies dedicate specific efforts to point pollution and effluent toxicity, particularly around the city of Iasi. For a better understanding of pollution and its effects, we recommend pursuing the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs) are toxic or carcinogenic compounds (Douben 2003) and have severely impacted local ecosystems and human health (Mumford et al 1987;Latimer and Zheng 2003;Shi et al 2007;Neamtu et al 2009;Hu et al 2011). They are emitted into the atmosphere by various combustion sources (Fernandes and Brooks 2003) or released into the aquatic environment through the discharges from human activities such as industrial or domestic sewage effluents (Burgess et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are toxic or carcinogenic compounds (Douben 2003) and have severely impacted local ecosystems and human health (Mumford et al 1987;Latimer and Zheng 2003;Shi et al 2007;Neamtu et al 2009;Hu et al 2011). They are emitted into the atmosphere by various combustion sources (Fernandes and Brooks 2003) or released into the aquatic environment through the discharges from human activities such as industrial or domestic sewage effluents (Burgess et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to EcSF-5-7, the measurement of ecological indices (Neamtu et al 2009) with planktonic algae and benthic invertebrates confirmed this degradation of river water downhill.…”
Section: Ecological Sustainability Filtermentioning
confidence: 53%
“…Contamination of the river sediments also indicated higher contamination levels in this area. Neamtu et al (2009) carried out similar measurements of POPs in sediments along the Bahlui River flowing nearby and found contamination levels in about the same range of concentration; they also found that contamination with POPs was stronger downhill from the landfill.…”
Section: Ecological Sustainability Filtermentioning
confidence: 79%
See 1 more Smart Citation
“…At this event, a proceedings publication with ten articles was presented (Panin and Giger 2008). All nine ESTROM projects are presented as summary reports in this Special Issue of Environmental Science and Pollution Research (Alexandrow and Bloesch 2009;Bravo et al 2009;Moldovan and Alder 2009;Neamtu et al 2009;Pavel et al 2009;Soutter et al 2009;Velea et al 2009;Zobrist et al 2009). The presentation files of the talks of the ESTROM meetings and the International Conference are available on the Internet (http://www.cnmp.ro/estrom_en.php?…”
mentioning
confidence: 99%